Timeliness and accuracy of information sharing from hospital information systems to electronic health record in Iran - Reza Abbasi (مدیریت سلامت, 2019)
Introduction: Inaccurate and delayed entry of information are one of the sources of failure in the communication of information between hospital information systems and electronic health record in Iran. The purpose of this study was to investigate the accuracy and timeliness rate of patients’ information in hospital information system whose information was not successfully sent to electronic health record system. Methods: In this descriptive study, conducted in 2016, 882 records which had failed to be sent from hospital information systems to electronic health record system were reviewed. A checklist was used to collect data which were then analyzed by SPSS.22 to calculate the frequency of accurate and timely data entry in hospital information systems. Results: A total of 18758 demographic and clinical information were examined. Overall, the accurate and timely data entry in hospital information systems were 97% and 99.87%, respectively. The highest rate of inaccurate information was related to patients’ identification numbers, national codes, full addresses and places of residence, and the highest rate of delayed data entry was related to final diagnosis and causes of patient death. Conclusion: The results demonstrated a high rate of accurate and timely data entry in hospital information systems. The results also identified some sources of inaccurate and delayed data entry which could be attributed to the negligence of the users. Therefore, it is recommended to hold orientation sessions to enhance users’ knowledge about accurate and timely data entry, and also design systems capable of producing feedback in order to improve the accuracy and timeliness of data entry.